1953
DOI: 10.1139/z53-016
|View full text |Cite
|
Sign up to set email alerts
|

A CYTOLOGICAL STUDY OF THE ANTERIOR SUBMAXILLARY GLANDS OF THE FOWL, GALLUS DOMESTICUS

Abstract: A cytological study was made of the anterior submaxillary gland of the domestic chicken a t 1 day, 4 days, and 10 months of age. This gland is one of a number of aggregates distributed throughout the mouth and along the oesophagus. I t is a compound tubular gland, whose ducts open in several places under the tongue. T h e glandular epithelium is a single layer of tall prismatic inucous cells. There are no serous cells. Most of the cells are loaded with mucus and the nuclei are flattened a t the bases of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The mucous glands at the laryngeal mound called cricoarytenoid salivary glands (King and Mclelland, 1984;Liman et al, 2001 andMohamed, 2004) while, Homberger and Meyers (1989) named these glands as laryngeal glands. As reported by McCallion and Aitken, (1953) in the fowl, the laryngeal glands of turkey were located within the lamina propria and their ducts penetrated the mucosa to open into the pharyngeal cavity. Each gland was formed from a varying number of units, each unit comprising many tubules which open into a common cavity and possessing a common duct.…”
Section: Discussionmentioning
confidence: 58%
“…The mucous glands at the laryngeal mound called cricoarytenoid salivary glands (King and Mclelland, 1984;Liman et al, 2001 andMohamed, 2004) while, Homberger and Meyers (1989) named these glands as laryngeal glands. As reported by McCallion and Aitken, (1953) in the fowl, the laryngeal glands of turkey were located within the lamina propria and their ducts penetrated the mucosa to open into the pharyngeal cavity. Each gland was formed from a varying number of units, each unit comprising many tubules which open into a common cavity and possessing a common duct.…”
Section: Discussionmentioning
confidence: 58%
“…This in agreement with our present studies indicated that some muscle fibers inserted between lobular capsules of the preglottal gland and lymphoid tissues are present between septa also in older ages. However, (Mccallion & Aitken, 1953) do not find any muscle fibers or lymphoid tissues within the capsule.…”
Section: Discussionmentioning
confidence: 71%